2014
DOI: 10.1039/c4lc00528g
|View full text |Cite
|
Sign up to set email alerts
|

Thermally-induced miniaturization for micro- and nanofabrication: progress and updates

Abstract: The field of micro- and nanofabrication has developed extensively in the past several decades with rising interest in alternative fabrication techniques. Growth of these areas has been driven by needs that remain unaddressed by traditional lithographical methods: inexpensive, upscalable, biocompatible, and easily integrated into complete lab-on-a-chip (LOC) systems. Shape memory polymers (SMPs) have been explored as an alternative substrate. This review first focuses on structure fabrication at the micron and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 113 publications
0
43
0
Order By: Relevance
“…We have previously demonstrated that self‐similar hierarchal wrinkled structures in metal thin films can be created via heat induced biaxial shrinking on shape memory polymers (SMPs), such as polystyrene(PS) . The buckling occurs due to the mismatches in stiffness between the SMP and the deposited material during the shrinking process . Spray gun deposition was used to deposit CNT thin films on SMP.…”
mentioning
confidence: 99%
“…We have previously demonstrated that self‐similar hierarchal wrinkled structures in metal thin films can be created via heat induced biaxial shrinking on shape memory polymers (SMPs), such as polystyrene(PS) . The buckling occurs due to the mismatches in stiffness between the SMP and the deposited material during the shrinking process . Spray gun deposition was used to deposit CNT thin films on SMP.…”
mentioning
confidence: 99%
“…Stress relaxation can also occur through thermal actuation of pre‐stressed “shape memory” polymer substrates . The thermally activated substrates consist of pre‐stretched thermoplastics (e.g., polystyrene, polyolefin), often known as “shrink film”.…”
Section: Wrinkling and Crumpling Of 2d Materials Films On Flat Substratesmentioning
confidence: 99%
“…In particular, thermoplastic SMPs are attractive due to their low cost and processability. Heating an unaltered amorphous polymer sheet above its T g , stretching the material, and cooling the sheet below T g stores strain in the polymer . Industrially, strained polymer sheets are made through numerous methods including blown film extrusion, roll‐to‐roll processing, or film casting .…”
Section: Introductionmentioning
confidence: 99%